APPROACHES TO RELIGION AND ISLAMIC STUDIES: THE DOCTRINAL AND PHILOSOPHICAL APPROACHES - Ariati, Fitri; Zulfikri; Retoliah, Retoliah (Albariq: Jurnal Pendidikan Bahasa Arab, 2024)
This study explored two prominent methodologies in the study of religion and Islam: the doctrinal and philosophical approaches. The doctrinal approach emphasized the sacred and immutable nature of Islamic teachings, viewing them as divine doctrines. While this method was vital for internal understanding among adherents, it required complementary perspectives to address contemporary challenges. Conversely, the philosophical approach applied systematic, rational, and universal thinking to uncover the deeper meanings and values within Islamic teachings. By integrating these approaches, the study demonstrated how Islamic studies could balance normative and empirical insights to adapt to modern societal needs. This interdisciplinary exploration highlighted the significance of contextualizing Islamic principles to promote interfaith harmony and foster intellectual engagement.